Magnetron Sputtered Non‐Toxic and Precious Element‐Free TiZrGe Metallic Glass Nanofilms with Enhanced Biocorrosion Resistance. Issue 26 (18th August 2022) - Sarac, Baran; Micusik, Matej; Putz, Barbara; Wurster, Stefan; Sharifikolouei, Elham; Xi, Lixia; Omastova, Maria; Spieckermann, Florian; Mitterer, Christian; Eckert, Jürgen
Abstract: The chemical composition and structural state of advanced alloys are the decisive factors in optimum biomedical performance. This contribution presents unique TiZrGe metallic glass thin‐film compositions fabricated by magnetron sputter deposition targeted for nanocoatings for biofouling prevention. The amorphous nanofilms with nanoscale roughness exhibit a large relaxation and supercooled liquid regions as revealed by flash differential scanning calorimetry. Ti68 Zr8 Ge24 shows the lowest corrosion (0.17 µA cm −2 ) and passivation (1.22 µA cm −2 ) current densities, with the lowest corrosion potential of −0.648 V and long‐range stability against pitting, corroborating its excellent performance in phosphate buffer solution at 37 °C. The oxide layer is comprised of TiO2, TiO x and ZrO x, as determined using X‐ray photoelectron spectroscopy by short‐term ion‐etching of the surface layer. The two orders of magnitude increase in the oxide and interface resistance (from 14 to 1257 Ω cm 2 ) along with an order of magnitude decrease in the capacitance parameter of the oxide interface (from 1.402 × 10 −5 to 1.677 × 10 −6 S s n cm −2 ) of the same composition is linked to the formation of carbonyl groups and reduction of the native oxide layer during linear sweep voltammetry. Abstract : Composition of magnetron sputtered TiZrGe metallic glass nanofilms can be tailored to achieve enhanced biocorrosion resistance, high passivation and supercapacitive behavior within phosphate‐buffered saline solution. Depletion of the oxide layer on the surface is due to the formation of OH groups at the cathodic potentials, where an increase in O1s CO and O1s CO signals after polarization is observed.